Adaptive changes of influenza virus A/H5N1 neuraminidase in vitro and in vivo - Le Nguyen, T (2014)
H5N1 adaptation process is thought to primarily involve in changes of the 2 main glycoproteins of influenza virus: hemagglutinin HA, responsible for viral entry via binding with host cell receptors, and neuraminidase NA, a receptor destroying enzyme, promoting release of newly formed virions and preventing their self-aggregation. With their opposing roles in viral replication cycle, one rational assumption is that influenza virus needs to maintain a balance between these 2 proteins activities to ensure productive infection. Because of their impacts on both viral evolution and drug susceptibility, it is necessary to gain insight into the interplay between HA and NA proteins as this will further our understanding of the cross-species A/H5N1 adaptation process, with or without selective pressure. One of the most suitable systems to study influenza adaptation is cultures of differentiated human epithelial cells; which have been used for more than 30 years in various types of research. This project aimed to set-up that system in our laboratory in Vietnam to passage H5N1 viruses in order to use in later studies monitoring the adaptive changes of those viruses, especially in the two major glycoproteins HA and NA. In parallel, H5N1 isolates with different oseltamivir susceptibility profile were investigated to gain clear insight on NA enzymatic properties as well as the underlying mechanism of resistance. Those H5N1 isolates were human clade 1 viruses from the period of 2004 - 2005 in south of Vietnam with different oseltamivir sensitivity. Recombinant variants, with NA derived from H5N1 viruses and other segments from laboratory adapted human seasonal strain WSN33, were generated by reverse genetic techniques and then characterized on NA enzymatic properties. We identified 2 NA mutations which were suspected to affect NA activity and/or expression. Further investigations are required to conclude whether these 2 substitutions might support or allow the virus(es) to overcome the deficiency caused by oseltamivir resistance mutation, resulting in adaptive evolution of influenza viruses.